2006
DOI: 10.1089/fpd.2006.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antibiotic Resistance Profiling ofSalmonellaIsolated from Retail Turkey Meat Products

Abstract: Contaminated poultry meat has been identified as one of the principal foodborne sources of Salmonella. Molecular characterization of Salmonella is important in addressing methods to control this pathogen. Seventy-four retail turkey meat samples were collected from various stores in Fargo, North Dakota in the fall of 2003. Salmonella was recovered from 30 samples using the standard conventional culture method (FSIS, USDA). Isolated Salmonella were characterized by serotyping, pulsed-field gel electrophoresis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
6
6
1
Order By: Relevance
“…Different prevalence rates of Salmonella spp. in food, especially poultry and poultry products, have been reported by different authors [12][13][14][15][16][17]. Salmonella contamination rates observed in our country are relatively high (22.92%) and confirm the widespread contamination of pork and chicken meat with Salmonella spp.…”
Section: Discussionsupporting
confidence: 84%
“…Different prevalence rates of Salmonella spp. in food, especially poultry and poultry products, have been reported by different authors [12][13][14][15][16][17]. Salmonella contamination rates observed in our country are relatively high (22.92%) and confirm the widespread contamination of pork and chicken meat with Salmonella spp.…”
Section: Discussionsupporting
confidence: 84%
“…4:12: nonmotile and S . Reading were recovered from retail turkey meat samples in North Dakota, USA [10]. Khaitsa et al [12] reported six Salmonella serotypes from 959 turkey products as follows: Hadar, Heidelberg, Typhimurium var.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies showed that prevalence and serotype distribution of Salmonella was varied. The percentage of positive samples varied from zero to 40% in fresh turkey meat and higher than 5% in RTE turkey meat products in EU countries, the US and the Canada [5, 1014]. The results of these studies showed that serotype profiles of the isolates were different.…”
Section: Introductionmentioning
confidence: 97%
“…DNA macrorestriction fragments were resolved on 1% SeaKem Gold agarose (Cambrex Bio Science Inc., Rockland, ME) in 0.5ϫ Tris-borate-EDTA. PFGE was carried out as previously described (11,53). Images were captured using a UV imager (Alpha Innotech, CA) and stored as .tif files.…”
Section: Methodsmentioning
confidence: 99%